Metode Dakwah Melalui Lembaga Masjid Studi Kasus Masjid Al-Muttaqin Tuban - Kahfi, Shofiyullahul; Rahmat Albustomi, Abdul (ASWALALITA: Journal of Da'wah Management, 2025)
The method of preaching is an effective way to explain strategically identified preaching. In this case, preaching in the mosque is not only limited to Friday sermons or sermons, but also involves various activities that can strengthen faith and increase religious knowledge of Muslims. Linguistic definition of technique The term "method" comes from Greek and is a mixture of the words "meta" (through) and "hodos" (path). In English, it means "method." In Arabic, "method" is called "tariq", while in German, "methodicay" means "path". Al-Muttaqin Mosque is located in a rural area and is one of the most famous mosques in the area. This mosque has quite complete facilities, including a main prayer room, a study room, and a fairly large parking lot. Overall, da'wah through the mosque institution, especially in the Al-Muttaqin Mosque, shows that the mosque is not only a place of worship, but also a center for social and educational activities that are very important in forming a better Muslim community, both in terms of spirituality and social.